From Competence to Agility: A Systematic Review of Digital Competence and Employee Agility Effects on Employee Performance in Digital Transformation Era - Munawaroh, Munawaroh; Khaerunnisa, Ratna; Mudaeroh; Galuh, Aryawa; Maulana, Adam (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
Accelerating digital transformation has fundamentally reshaped employee competency requirements and work-related behaviors, compelling organizations to develop workforces that are both digitally proficient and highly adaptive. This study aims to systematically synthesize empirical evidence regarding the influence of digital competence and employee agility on employee performance across diverse organizational contexts. A systematic literature review was conducted following the PRISMA guidelines. Relevant peer-reviewed articles published between 2021 and 2025 were identified through comprehensive searches of Scopus- and Sinta-indexed databases. A rigorous multi-stage screening and eligibility process resulted in the selection of ten high-quality studies, which were subsequently analyzed using thematic analysis techniques. The findings indicate that digital competence generally exerts a positive influence on employee performance, operating through both direct effects and indirect mechanisms such as enhanced work efficiency, innovation, and technology utilization. However, the strength and consistency of these effects vary across organizational settings and sectors. In contrast, employee agility emerges as a more consistent and robust predictor of employee performance, functioning as a critical adaptive capability that bridges digital competencies with effective work outcomes in dynamic environments. Despite these insights, the reviewed literature reveals several limitations, including fragmented theoretical frameworks, inconsistent empirical findings, a predominance of cross-sectional research designs, and limited contextual diversity. This review contributes an integrated understanding of the complementary roles of digital competence and employee agility in shaping employee performance. Furthermore, it highlights the need for conceptual model development and methodological diversification in future research. The synthesis offers evidence-based guidance for organizations navigating human resource management challenges in the digital era by emphasizing the balanced development of digital capabilities and adaptive capacities to achieve sustainable performance improvement.